2019
DOI: 10.2503/hortj.utd-045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abscisic Acid/Ethephon Treatments on Berry Development and Maturation in the Yellow-green Skinned ‘Shine Muscat’ Grape

Abstract: Abscisic acid (ABA) and ethylene are well-known phytohormones that are involved in the maturation of grape berries and other fruits. However, the process of yellow-green skinned grape berry maturation is not well understood due to difficulties in determining grape maturity from changes in skin color. Skin browning during maturation is a major commercial problem in some yellow-green skinned grape cultivars including 'Shine Muscat'. To resolve this issue, a better understanding of the mechanisms involved in grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…In this study, CPPU treatment was more effective than GA 3 treatment at the veraison stage, although the application concentrations were different. Berry maturation was delayed by GA/CK treatment and this was the opposite result of ABA/ethephon treatment (Suehiro et al, 2019). Brassinosteroid and jasmonic acid have also been reported to promote grape berry maturation and ripening (Jia et al, 2016;Symons et al, 2006).…”
Section: Effects Of Ga/ck Treatment On Berry Properties and Chlorophymentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, CPPU treatment was more effective than GA 3 treatment at the veraison stage, although the application concentrations were different. Berry maturation was delayed by GA/CK treatment and this was the opposite result of ABA/ethephon treatment (Suehiro et al, 2019). Brassinosteroid and jasmonic acid have also been reported to promote grape berry maturation and ripening (Jia et al, 2016;Symons et al, 2006).…”
Section: Effects Of Ga/ck Treatment On Berry Properties and Chlorophymentioning
confidence: 97%
“…The degree of skin browning in each whole berry cluster was determined based on criteria developed by Mochida et al (2013). Individual berries were assigned to categories of browning as indicated in Suehiro et al (2019).…”
Section: Measurement Of Berry Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been demonstrated in grapes, where berries exposed to exogenous applications of CK and GA at veraison grow larger fruits and accumulate lower amounts of hexose sugars during ripening. In treated berries, downregulation of ABA and ethylene biosynthesis was directly correlated with reduced color changes and prolonged greenness in the fruit pericarp, whereas ABA and ethylene signaling were unsuppressed in control fruits that exhibited unperturbed ripening (Suehiro et al ., 2019).…”
Section: Ripeningmentioning
confidence: 99%
“…The role of various transport systems in ABA translocation, stomatal, cuticular, and root responses, and also osmotic adjustment has been summarised by Jarzyniak and Jasiński (2014). In contrast, other reports have shown that VvNCED1 was upregulated by ABA and ethephon treatments (Pilati et al, 2017;Suehiro et al, 2019), explaining the intracellular ABA level measured by Pilati et al (2017).…”
Section: Oxalic Acid Preharvest Treatment Upregulates Abscisic Acid Metabolism Relative Vvnced1 Gene Expression and Antioxidant Enzyme Acmentioning
confidence: 99%